2009
DOI: 10.1055/s-0029-1217095
|View full text |Cite
|
Sign up to set email alerts
|

Paternò-Büchi Reactions of Silyl Enol Ethers and Enamides

Abstract: 3-(Silyloxy)oxetanes are obtained by irradiating mixtures of aromatic aldehydes and silyl enol ethers in benzene as the solvent. The reactions occur with high simple diastereoselectivity and, when R 1 is chiral, with high facial diastereoselectivity. Under similar conditions, but in acetonitrile rather than benzene as the preferred solvent, the Paternò-Büchi reaction of N-acyl enamines (enamides) gives the corresponding protected 3-aminooxetanes. The cis-products are obtained with significant simple diastereos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…As an extension of their previous studies on [2+2] photocycloadditions of enamines to aldehydes, 15 in 2001, Bach and co-workers examined the synthesis of 3-aminooxetanes via a Paternò-Büchi reaction of enecarbamates and benzaldehyde. 16 UV irradiation of enecarbamates 39 and benzaldehyde in acetonitrile led to the formation of 3-aminooxetanes 40 in good yields with high regioselectivity and as a cis/trans mixture (Scheme 6).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…As an extension of their previous studies on [2+2] photocycloadditions of enamines to aldehydes, 15 in 2001, Bach and co-workers examined the synthesis of 3-aminooxetanes via a Paternò-Büchi reaction of enecarbamates and benzaldehyde. 16 UV irradiation of enecarbamates 39 and benzaldehyde in acetonitrile led to the formation of 3-aminooxetanes 40 in good yields with high regioselectivity and as a cis/trans mixture (Scheme 6).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…The resultant water is removed using azeotropic distillation [116] or molecular sieves (4 Å) [113], P 2 O 5 /SiO 2 [117], MgSO 4 [118,119], or TiCl 4 [119] that also catalyze the reaction as Lewis acids. Sometimes, the reaction is carried out on cooling in the absence of catalyst and dehydrating agent [109].…”
Section: Condensation Of Carbonyl Compound With Aminesmentioning
confidence: 99%
“…The area of photochemistry has seen the use of enamides as substrates in the Paterno-B üchi photochemical reaction. 42 Bach has demonstrated that enecarbamates participate particularly well, forming amino oxetanes 23 in good yield with significant diastereoselectivity (Scheme 19). This research group has also achieved an analogous transformation using nitriles, replacing the ynol ethers, as a versatile entry to pyrimidines.…”
Section: Photochemical Reactionsmentioning
confidence: 99%